Comparison of the Effect of Extracted Bacteriocin and Lytic Bacteriophage on the Expression of Biofilm Associated Genes in Streptococcus mutans - Zahra Rajabi; Mohammad Mehdi Soltan Dallal; Mohammad Reza Afradi; Yousef Erfani; Donya Alinejad; Reza Ranjbar; Rouha Kasra-Kermanshahi (Advances in Materials Science and Engineering)
Today, various biological approaches are used to combat dental plaque biofilms. In the current study, we aimed to compare the effect of extracted bacteriocin and lytic bacteriophage on the expression of biofilm associated genes in Streptococcus mutans. Streptococcus mutans was isolated from plaques of decayed dental and the existence of their gtfs genes was confirmed by PCR. For bacteriocin extraction, at first two probiotic lactobacilli were isolated from traditional foods, then bacteriocin was extracted by partial purification method, and SDS-PAGE was used for estimation of its molecular weight. The previously extracted lytic bacteriophage from raw urban sewage was used against Streptococcus mutans. Finally, the effect of isolated bacteriocin and bacteriophage on gtfs genes expression level was measured by real-time PCR. Out of 81 dental plaque samples, 32 (39.5%) Streptococcus mutans strains were isolated. The frequency of genes was as follows: gtfD32 (100%), gtfB 17 (53.12%), and gtfC 19 (53.37%). 120 traditional food samples (milk, yogurt, pickle, and salty pickle) were evaluated for isolation of lactobacillus. Three strains of Lactobacillus fermentum and four Lactobacillus plantarum with probiotic potential activity were isolated. Two types of bacteriocins from Lactobacillus fermentum and a single type of bacteriocin from Lactobacillus plantarum were extracted, and their molecular weights were 60, 58, and 70 kDa, respectively. In our previous study, two bacteriophages belonging to the Siphoviridae and Tectiviridae families were isolated. Real-time PCR results had shown that both bacteriocin and bacteriophage had a decreasing effect on the expression of gtfs genes. The different modes in our study for the effects of bacteriocin and bacteriophage showed that both of them had good potential as suitable options to fight dental plaque biofilms, and bacteriophages alone showed a stronger reducing effect.